Một số giải pháp quản lý nhằm bảo vệ và phát triển rừng ở Tây Nguyên - Phạm, Quang Duễ (2011)
Tác giả: Phạm Quang Duễ, ThS; Nguyễn Thế Tràm, TS; Phạm Hảo, PGS-TS; Trương Minh Dục, TS; Lê Văn Hải, ThS; Phạm Quốc Tuấn, ThS -- Từ khóa: Bảo vệ rừng; Tây Nguyên